Understanding electrolysis - Burns, Pru.; Garner, Simon; Lines, Jeremy; McKenzie, Ben.; Video Educaiton Australasia (Bendigo, Vic. : Video Education Australasia, 2010)
"Electrolysis has important applications in everyday life - from the batteries in our portable devices to the production of common metals such as aluminium. Featuring lab demonstrations, engaging graphics and clear explanations, this program looks at the chemistry of electrolysis. Two types of electrochemical cells are introduced - galvanic cells and electrolytic cells - and compared. The program discusses the industrial applications of electrochemistry, including brine electrolysis, aluminium production, electroplating and anodising. Viewers are also introduced to the many applications of rechargeable batteries, such as lead-acid, Ni-MH and Li-ion batteries before concluding with an introduction to Faraday's First Law of Electrolysis and stoichiometric calculations." - VEA website.
Director/writer/produer is Jeremy Lines ; senior producer is Pru Burns ; executive producer is Simon Garner.
Presenter is Ben McKenzie.
Keywords: Chemistry, Analytic; Electrochemistry; Electrolysis